1977
DOI: 10.1901/jaba.1977.10-345
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Teachers as Behavioral Observers

Abstract: The effect of using teachers as behavioral observers on both student and teacher behavior was examined with eight teachers and 32 elementary school children. The frequency of prompts (but not praise or criticism) to those students observed by the teacher increased significantly from nonobserver to teacher observed experimental phases. In addition, students observed by the teacher showed more change in appropriate behavior than students who were not observed. The significance of these findings for research and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…It was found that after teachers began to measure pupil performance, there was no therapeutic change in their behavior. A similar result was reported by Hay et al (1977). They found that after training to record pupil classroom behavior, teachers changed their behavior, but not in ways that improved pupil behavior.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It was found that after teachers began to measure pupil performance, there was no therapeutic change in their behavior. A similar result was reported by Hay et al (1977). They found that after training to record pupil classroom behavior, teachers changed their behavior, but not in ways that improved pupil behavior.…”
Section: Discussionsupporting
confidence: 80%
“…Reports of "baseline cure" (Forehand, 1973) and teacher reactivity to measuring pupil behavior (Hay, Nelson, & Hay, 1977) Teachers taught classes of three "multihandicapped" pupils who were characterized by behavioral, emotional, and learning problems in addition to a tested hearing loss. The two boys and one girl in each classroom ranged in age from 8 yr 3 mo, to 10 yr 4 mo, with an average age of 9 yr 7 mo.…”
mentioning
confidence: 99%
“…The author then provided feedback to the instructor on accuracy in emitting the 12 responses required for discrete-trial teaching. Video was used in order to decrease the likelihood of reactivity (Hay, et al, 1977). Each session was defined as the presentation of one educational program using 10 discrete trials.…”
Section: Staff Training Proceduresmentioning
confidence: 99%
“…Most important for evaluating aggression or other inappropriate behavior, the typical effect of reactivity is a move toward social desirability, which can be expected to substantially reduce the display of the behavior of interest. Some early work with aggressive elementary school children suggested that the presence of an adult observer caused children to change their behavior in the classroom as well as in play settings (Hay, Nelson, and Hay, 1977;Martin, Gelfand, and Hartmann, 1971).…”
Section: Why Observation?mentioning
confidence: 99%